Shinjuku as site: Funeral Parade of Roses and Diary of a Shinjuku Thief. (March 2014) - Nettleton, Taro
Abstract : Regarded by one critic as a 'first-rate second-rate neighbourhood', Shinjuku, a ward located in the geographical centre of Tokyo has, since the 1960s, been both site and subject of numerous aesthetic, political, and sexual experimentations. Many key figures of Japanese underground postwar visual culture, such as pink film director Wakamatsu Koji, photographer Moriyama Daido, and playwright Terayama Shuji have made work in and about the neighborhood. This essay considers the growing importance of Shinjuku primarily through two films, which it frames as variants of the city symphony: Oshima Nagisa's Shinjuku Dorobo Nikki/Diary of a Shinjuku Thief (1969) and Matsumoto Toshio's Bara no Soretsu /Funeral Parade of Roses (1969). Today, Shinjuku of the 1960s tends to be nostalgically portrayed as an unfettered site of experimentation and freedom. Shinjuku had indeed, at the time of the films' production, become an important site for various cultural experimentations, but it was also promoted primarily for business interests. As a result, the meaning and uses of Shinjuku, which functioned as a site of multiple antagonisms, were contested. It was within such a context that Oshima and Matsumoto made their respective films, which treat Shinjuku as one of their main players. Matsumoto and Oshima both framed their respective films as political texts. While both films address relationships between art, politics, and sexuality, they do so in very different ways. I propose that the films suggest Matsumoto's and Oshima's conflicting views on what counted as 'politics', 'political art', and who counted as Shinjuku's rightful inhabitants.